Oral and intestinal manifestations of giant cell arteritis - Mathieu Pernet; Laura Moi; Fulvia Serra; Nicolas Garin (European Journal of Case Reports in Internal Medicine)
Background: Giant cell arteritis (GCA) is the most common primary vasculitis in individuals over 50 years of age. GCA typically affects large- and medium-sized arteries and is classically associated with cranial manifestations of ischaemia, such as headaches (notably in the temporal region), jaw claudication and visual symptoms that can lead to blindness. Extracranial symptoms are less frequently reported and are related to involvement of the thoracic and abdominal aorta and its main branches. Classic diagnostic tools (such as temporal artery ultrasonography and temporal artery biopsy) can be negative in extracranial GCA. Case description: We report a difficult diagnosis of GCA in a 75-year-old woman who developed painful tongue ulcers that responded to prednisone treatment. However, a comprehensive diagnostic work-up did not lead to a certain diagnosis of GCA and corticosteroids were stopped after one month. A few months later, the patient suffered from mechanical ileus secondary to ischaemic stenosis of the small bowel. Pathological examination of the small bowel resection, and a second FDG-PET/CT, led to the diagnosis of extracranial GCA. Conclusions: We present a case of CGA which sequentially affected cranial and extracranial arteries and illustrate pitfalls in the diagnosis of this polymorph condition.